In vitro methane and carbon dioxide production of tropical grasses of the coast of Oaxaca, Mexico - Camacho-Escobar, Marco Antonio; Galicia-Jiménez, Mónica Marcela; Sánchez-Bernal, Edgar Iván; Ávila-Serrano, Narciso Ysac; López-Garrido, Serafín Jacobo (REVISTA TERRA LATINOAMERICANA, 2020)
Tropical grasses have different chemical composition; when they are fermented in rumen, they show different values in digestibility, volatile fatty acid concentration (VFA), and methane (CH4) and carbon dioxide (CO2) production. The objective of this study was to determine the chemical composition, characterize fermentation, and estimate CH4 and CO2 emissions in vitro in tropical grasses of Oaxaca. For the experiment, 0.5 g of dry matter of the grasses Cynodon nlemfuensis, Andropogon gayanus, Pennisetum purpureum cv. Taiwan Morado, Pennisetum purpureum cv. Maralfalfa and Panicum maximum were incubated with 45 mL of culture medium for anaerobic microorganisms and deposited in 100 mL glass vials with CO2 flow. The grasses were inoculated with 5 mL of rumen fluid and incubated at 39 °C for 72 h. Biogas production and microorganism population were determined at 6, 12, 24, 48, and 72 h. Volatile fatty acid (VFA) concentrations, pH and in vitro dry matter degradability (IVDMD) were determined at 72 h. CH4 and CO2 emissions were estimated at 24, 48, and 72 h. The response variables were evaluated by a completely randomized design with five replicates per treatment; the comparison of means was made with Tukey’s test. C. nlemfuensis had the highest (P < 0.05) crude protein content. The cellulolytic bacterial population was lower (P < 0.05) in Andropogon gayanus and Panicum maximum. Cynodon nlemfuensis, Andropogon gayanus and Pennisetum purpureum cv. Taiwan Morado had lower (P < 0.05) acetate concentrations; Panicum maximum had higher (P < 0.05) propionate concentration. Pennisetum purpureum cv. Maralfalfa showed the highest (P < 0.05) IVDMD and produced the lowest (P < 0.05) CH4 volumes; Cynodon nlemfuensis and Panicum maximum produced lower CO2 volumes.